Komunikace osob s duálním smyslovým postižením Metodické texty k projektu MUNI 4.0. Pedagogická fakulta, studijní program Logopedie (Bc.) - Horáková, Radka (Masaryk University Press, 2019)
Title in English: Communication of the persons with dual sensory disability: Methodical texts for the MUNI 4.0 project The aim of the given text is to introduce elementary concept concerning the topic of deafblindness. Dual hearing and visual impairment is considered to be one of the most serious combined disability in general. The text is divided into three parts that relate to one other. The first chapter content is basic characteristic of the person with dual sensory disability and there are also included causes of the deafblindness. In the second chapter student will become familiar about communication systems as well as communication strategies in people with hearing and visual impairment. The third chapter is devoted to the possibilities in the education process and care about clients with deafblindness.